The Human brain is best described as being on a female/male continuum: evidence from a neuroimaging connectivity study - Zhang, Yi; Luo, Qiang; Huang, Chu-Chung; Lo, Chun-Yi Zac; Langley, Christelle; Desrivières, Sylvane; Quinlan, Erin Burke; Banaschewski, Tobias; Millenet, Sabina; Bokde, Arun L W; Flor, Herta; Garavan, Hugh; et al. (Cerebral cortex, 2021)
Psychological androgyny has long been associated with greater cognitive flexibility, adaptive behavior, and better mental health, but whether a similar concept can be defined using neural features remains unknown. Using the neuroimaging data from 9620 participants, we found that global functional connectivity was stronger in the male brain before middle age but became weaker after that, when compared with the female brain, after systematic testing of potentially confounding effects. We defined a brain gender continuum by estimating the likelihood of an observed functional connectivity matrix to represent a male brain. We found that participants mapped at the center of this continuum had fewer internalizing symptoms compared with those at the 2 extreme ends. These findings suggest a novel hypothesis proposing that there exists a neuroimaging concept of androgyny using the brain gender continuum, which may be associated with better mental health in a similar way to psychological androgyny.